Hongos liquenizados hallados sobre restos arqueológicos: nuevos registros para la provincia de Santa Cruz y un nuevo registro para Argentina - García, Renato Andrés (2015)
As part of an anthropological study, the lichenized fungi on the surface of archaeological remains from La Primavera locality in Santa Cruz province, Argentina, were identified. To achieve this, external morphological characters were observed and handmade cuts of apothecia were observed under light microscope; also the spot tests with K (potassium hydroxide), C (sodium hypochlorite) and reaction under UV light were performed. As a result, 16 species of which 2 previously cited for the province, 13 are new records for the province and Carbonea vorticosa is a new record for the country. Identifying species that grow on this type of anthropogenic substrate is relevant both for future floristic, ecological and biogeographical studies as well as for archaeological studies.